A method for preparing a non-iridescent structural color material with high saturation and high brightness
Through the shear-induced self-assembly method of inorganic nanoparticles at room temperature, the problem of low brightness and low saturation of non-irradiance photonic crystal structure color materials is solved, and a non-irradiance structure color material with high saturation and brightness is achieved. Suitable for a variety of application areas.
Patent Information
- Application Number
- CN202310322488.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The application of existing non-irradiant photonic crystal structure color materials in wide-angle display, coatings and cosmetics fields is limited by the problems of low brightness and low saturation.
By induced self-assembly by using inorganic nanoparticles with high refractive index at room temperature, a short-range ordered but long-range disordered structure is formed, effectively absorbing incoherent scattering, thereby improving the brightness and saturation of structural color materials.
It achieves high saturation and brightness non-irradiant structured films and pigments, with low angle dependence, single color and no impurities, suitable for wide-angle display, coatings and textile fields.
Smart Images

Figure CN116376323B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photonic crystal structural color material preparation, and in particular relates to a method for preparing a non-iridescent structural color material. Background Art
[0002] Since S. John and E. Yablonovitch proposed the concept of photonic crystals in 1987, this kind of artificial optical structural color material with photonic energy bands and band gaps has shown great application prospects. Photonic crystals are generally formed by the periodic arrangement of two or more materials with different refractive indices in space, and have brighter structural colors and metallic luster than traditional dyes and pigments. However, due to the orderly spatial structure of traditional photonic crystals, they generally show iridescent structural colors, that is, the color of photonic crystals changes significantly with the change of observation angle. Specifically, as the observation angle increases, the color of photonic crystals will gradually change from red to blue, which greatly limits its application in wide-angle displays, coatings or cosmetics.
[0003] As another type of amorphous structure that exhibits structural colors, non-iridescent photonic crystals achieve angle independence and wide-angle display through a long-range disordered but short-range ordered structure formed by the amorphous arrangement of nanoparticles in space. Generally speaking, non-iridescent photonic crystals exhibit structural colors through the coherent scattering of light by the amorphous structure. However, due to the presence of the amorphous structure, some strong incoherent scattering will occur, which will reduce the color saturation of the photonic crystals and even appear pale, greatly limiting the application of such photonic crystals. By adding light-absorbing materials such as carbon black, gold nanoparticles or polypyrrole, the incoherent scattering can be greatly reduced, thereby improving the saturation of non-iridescent structural colors; however, the presence of light-absorbing materials will also reduce the brightness of the photonic crystals. Therefore, people hope to develop a photonic crystal structural color film and pigment that has both high saturation and brightness and non-iridescent characteristics. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing non-iridescent structural colors with high saturation and brightness.
[0005] The non-iridescent structural color material provided by the present invention includes a film and a pigment in specific form, and is composed of inorganic nanoparticles with a high refractive index. The movement of the nanoparticles is induced by shearing action, and a short-range ordered but long-range disordered structure is quickly formed at room temperature. At the same time, the inorganic nanoparticles with a high refractive index can be used as a light-absorbing material to effectively absorb incoherent scattering, thereby solving the problem of low brightness of non-iridescent structural color films and pigments while maintaining high saturation.
[0006] The preparation method of the non-iridescent structural color material provided by the present invention uses inorganic nanoparticles with high refractive index as primitives and small molecules mediate shear-induced self-assembly at room temperature to obtain a non-iridescent photonic crystal structural color material (film and pigment), and the specific steps are as follows:
[0007] (1) Preparation of structural color paste
[0008] The surface of inorganic nanoparticles with a high refractive index is modified, and then mixed evenly with a small molecule organic matrix to form a structural color paste with high viscoelasticity;
[0009] (2) Preparation of non-iridescent structural color films and pigments
[0010] The structural color slurry obtained in step (1) is allowed to stand for a period of time to increase the interaction between the nanoparticles and the matrix, and then the slurry is sandwiched between two layers of PET or between two rollers, and a certain shear force is applied using a double-roll mill. After solidification, a non-iridescent structural color film is obtained, and the non-iridescent structural color pigment is obtained by grinding the film.
[0011] Further,
[0012] In step (1), the inorganic nanoparticles with a high refractive index include but are not limited to ferrosoferric oxide (Fe3O4), cuprous oxide (Cu2O), zinc oxide (ZnO), zinc sulfide (ZnS), cadmium sulfide (CdS) and titanium dioxide (TiO2).
[0013] In step (1), the particle size of the inorganic nanoparticles can be controlled to be 100 to 300 nm. As a further preferred embodiment, when the particle size of the nanoparticles is 120 to 240 nm, a non-iridescent structural color film in the visible light range can be obtained.
[0014] In step (1), the method for modifying the surface of the nanoparticles includes but is not limited to coating the outside of the nanoparticles with a polymer shell layer of a certain thickness to form a core-shell structured microsphere, wherein the polymer includes but is not limited to hydroxyethyl methacrylate (HEMA), acrylic acid (AA), ethyl acrylate (EA), methacrylic acid (MAA), butyl acrylate (BA), isooctyl acrylate (2-EHA), etc.; the surface of the nanoparticles is modified with functional groups that can produce intermolecular interactions with subsequent small molecule organic matrix, wherein the functional groups include but are not limited to hydroxyl (-OH), amino (-NH2), carboxyl (-COOH), carbonyl (-C=O), etc.
[0015] In step (1), the small molecule organic matrix includes but is not limited to hydroxyethyl methacrylate (HEMA), acrylic acid (AA), ethyl acrylate (EA), methacrylic acid (MAA), butyl acrylate (BA), methyl methacrylate (MMA), methyl acrylate (MA), methylformamide (MA), etc.
[0016] In step (1), the method for producing a high-viscoelastic slurry includes but is not limited to mutual swelling or supramolecular interaction between the modified inorganic nanoparticles and the organic matrix; adding another component polymer to the system that can increase the interaction between the nanoparticles and the matrix. Preferably, this component polymer includes but is not limited to polyethyleneimine (PEI), polystyrene-maleic anhydride copolymer (PSSMA), etc.
[0017] In step (2), the inorganic nanoparticles and the organic matrix are mixed and allowed to stand for 0 to 30 hours, preferably for 5 to 30 hours, and more preferably for 20 to 24 hours.
[0018] In step (2), the distance between the two rolls of the double-roll mill is 0.6-1 mm, so as to control the constant shear force.
[0019] In step (2), the applied shear force is 0.08 to 0.15 MPa.
[0020] Compared with the prior art and achievements, the beneficial effects of the present invention are:
[0021] (1) The present invention uses inorganic nanoparticles with high refractive index and light absorption characteristics to induce self-assembly under the action of shear force to prepare a low-angle-dependent structural color film, which exhibits high saturation and brightness, and also shows the low-angle-dependent characteristics of non-iridescence. In addition, the color is single and does not contain other impurity colors. It can be directly observed by the naked eye, solving the problem of low saturation of non-iridescent structural color films.
[0022] (2) The non-iridescent structural color film prepared by the present invention does not require high uniformity of the particle size of the building blocks, that is, the particle size of the inorganic nanoparticles can be distributed within a certain range, which optimizes the problem of requiring monodisperse nanoparticles in the shear induction process and greatly reduces the preparation requirements of the nanoparticles;
[0023] (3) The reason why the non-iridescent structural color film prepared by the present invention exhibits low angle dependence is that inorganic nanoparticles with uneven particle size distribution have relative slip under the action of shear force, forming a short-range ordered arrangement structure; at the same time, the Mie resonance scattering coherence caused by the amorphous arrangement of inorganic nanoparticles is enhanced, and incoherent scattering can be well absorbed, which provides a new idea for the preparation of high-saturation structural color films with low angle dependence;
[0024] (4) The non-iridescent structural color film provided by the present invention will not pollute the environment during the preparation process, the process is simple and easy, and no special equipment is required. It has application prospects in the fields of wide-angle display, coatings and textiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 are the reflection wavelengths of three different low-angle-dependent structural color films of green, yellow and red in Example 1, Example 2 and Example 3.
[0026] Figure 2 These are photos taken at different angles of three different low-angle-dependent structural color films of green, yellow and red in Example 1, Example 2 and Example 3.
[0027] Figure 3 It is the maximum reflection wavelength at different angles of three different low-angle-dependent structural color films of green, yellow and red in Example 1, Example 2 and Example 3.
[0028] Figure 4 The scanning electron microscope (SEM) images and the fast Fourier transform images (FFT) based thereon of three different low-angle-dependent structural color films of green, yellow and red in Example 1, Example 2 and Example 3 show an amorphous short-range ordered but long-range disordered structure.
[0029] Figure 5 is the reflection wavelength of different non-iridescent structural color films in Example 4, Example 5 and Example 6.
[0030] Figure 6 The reflection wavelength and photograph of the low-angle-dependent green structural color film obtained after the slurry formed by completely mixing the Fe3O4@(PHEMA-co-PEA) nanoparticles and hydroxyethyl methacrylate (HEMA) in Example 7 was allowed to stand for 0 to 30 hours.
[0031] Figure 7 These are photographs of the structural color coating prepared with the non-iridescent structural color pigment obtained in Example 8 at different angles. DETAILED DESCRIPTION
[0032] The present invention is further described below by way of embodiments in conjunction with the accompanying drawings.
[0033] Example 1
[0034] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.43 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally ferroferric oxide nanoparticles with a particle size of 142 nm were obtained. Then 200 m 1 g of ferrosoferric oxide nanoparticles were dispersed in 190 mL of acetonitrile (ACN) and ultrasonicated for 5 min. Then, 520 μL of ethyl acrylate (EA), 740 μL of hydroxyethyl methacrylate (HEMA), 300 mg of methylenebisacrylamide (MBA) and 30 mg of azobisisobutyronitrile (AIBN) were added and ultrasonicated for 10 min. Then, the dispersion was refluxed and precipitated at 110 °C for 2 h. The obtained Fe3O4@(PHEMA-co-PEA) nanoparticles were washed 3 times with ethanol and deionized water respectively.
[0035] (2) 200 mg of Fe3O4@(PHEMA-co-PEA) nanoparticles obtained in step (1) and 82 μL of hydroxyethyl methacrylate (HEMA) were thoroughly mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 70 wt % at this time. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a green low-angle-dependent non-iridescent structural color film with a reflection wavelength of 521 nm. The structural color film showed similar green photos at different angles (0°, 10°, 20°, 30°, 40°, 50°, 60°). (The reflection wavelength is as follows: Figure 1 As shown in Example 1, photos from different angles are as follows Figure 2 as shown in Example 1).
[0036] Example 2
[0037] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.42 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally ferroferric oxide nanoparticles with a particle size of 150 nm were obtained. Then 200 m 1 g of ferrosoferric oxide nanoparticles were dispersed in 190 mL of acetonitrile (ACN) and ultrasonicated for 5 min. Then, 520 μL of ethyl acrylate (EA), 740 μL of hydroxyethyl methacrylate (HEMA), 300 mg of methylenebisacrylamide (MBA) and 30 mg of azobisisobutyronitrile (AIBN) were added and ultrasonicated for 10 min. Then, the dispersion was refluxed and precipitated at 110 °C for 2 h. The obtained Fe3O4@(PHEMA-co-PEA) nanoparticles were washed 3 times with ethanol and deionized water respectively.
[0038] (2) 200 mg of Fe3O4@(PHEMA-co-PEA) nanoparticles obtained in step (1) and 82 μL of hydroxyethyl methacrylate (HEMA) were thoroughly mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 70 wt % at this time. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a yellow low-angle-dependent non-iridescent structural color film with a reflection wavelength of 564 nm. The structural color film showed similar yellow photos at different angles (0°, 10°, 20°, 30°, 40°, 50°, 60°). (The reflection wavelength is as follows: Figure 1 As shown in Example 2, photos from different angles are as follows Figure 2 (as shown in Example 2).
[0039] Example 3
[0040] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.41 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally ferroferric oxide nanoparticles with a particle size of 170 nm were obtained. Then 200 m 1 g of ferrosoferric oxide nanoparticles were dispersed in 190 mL of acetonitrile (ACN) and ultrasonicated for 5 min. Then, 520 μL of ethyl acrylate (EA), 740 μL of hydroxyethyl methacrylate (HEMA), 300 mg of methylenebisacrylamide (MBA) and 30 mg of azobisisobutyronitrile (AIBN) were added and ultrasonicated for 10 min. Then, the dispersion was refluxed and precipitated at 110 °C for 2 h. The obtained Fe3O4@(PHEMA-co-PEA) nanoparticles were washed 3 times with ethanol and deionized water respectively.
[0041] (2) 200 mg of Fe3O4@(PHEMA-co-PEA) nanoparticles obtained in step (1) and 82 μL of hydroxyethyl methacrylate (HEMA) were thoroughly mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 70 wt % at this time. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a red low-angle-dependent non-iridescent structural color film with a reflection wavelength of 687 nm. The structural color film showed similar red colors at different angles (0°, 10°, 20°, 30°, 40°, 50°, 60°). (The reflection wavelength is as follows: Figure 1 As shown in Example 3, photos from different angles are as follows Figure 2 (as shown in Example 3).
[0042] Example 4
[0043] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.43 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal autoclave. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally tetrahydrofuran nanoparticles with a particle size of 142 nm were obtained. ferroferric oxide nanoparticles; then disperse 200 mg of ferroferric oxide nanoparticles in 40 mL of anhydrous ethanol (EtOH) and 10 mL of deionized water, ultrasonicate for 5 minutes, then add 1.5 mL of γ-aminopropyltriethoxysilane (APTES) and 1.5 mL of ammonia water (NH3·H2O), ultrasonicate for 10 minutes, then stir the dispersion at 50°C for 24 hours, and wash the obtained Fe3O4-NH2 nanoparticles with ethanol and deionized water for 3 times each;
[0044] (2) 200 mg of Fe3O4-NH2 nanoparticles obtained in step (1) and 63 μL of methyl methacrylate (MAA) were completely mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 70 wt % at this time. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a cyan low-angle-dependent non-iridescent structural color film with a reflection wavelength of 503 nm. The reflection wavelength of the structural color film is similar to that of the photograph. Figure 5 As shown in Example 4.
[0045] Example 5
[0046] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.42 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally tetrahydrofuran nanoparticles with a particle size of 150 nm were obtained. Fe3O4-NH2 nanoparticles; then 200 mg of Fe3O4 nanoparticles were dispersed in 40 mL of anhydrous ethanol (EtOH) and 10 mL of deionized water, and ultrasonicated for 5 minutes, followed by the addition of 1.5 mL of γ-aminopropyltriethoxysilane (APTES) and 1.5 mL of ammonia water (NH3·H2O), and ultrasonicated for 10 minutes, and then the dispersion was stirred at 50 ° C for 24 hours, and the obtained Fe3O4-NH2 nanoparticles were washed 3 times with ethanol and deionized water. Then the obtained nanoparticles were dried and redispersed in N, N-dimethylformamide (DMF), and then 0.2 g of succinic anhydride was added, and the reaction was carried out at room temperature for 24 hours. The obtained Fe3O4-COOH nanoparticles were washed 3 times with ethanol and deionized water;
[0047] (2) 200 mg of Fe3O4-COOH nanoparticles obtained in step (1) and 63 μL of hydroxyethyl methacrylate (HEMA) were completely mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 75 wt % at this time. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a yellow-green low-angle-dependent non-iridescent structural color film with a reflection wavelength of 549 nm. The reflection wavelength of the structural color film and the photograph are as shown in FIG. Figure 5 As shown in Example 5.
[0048] Example 6
[0049] (1) 0.35 g of copper acetate monohydrate (Cu(AC)2·H2O), 0.41 g of sodium citrate dihydrate (Na3Cit·2H2O), and 1.5 g of polyvinylpyrrolidone (PVP) were dissolved in 100 mL of deionized water and 27 mL of ethylene glycol (EG). After stirring, 20 mL of 0.5 M sodium hydroxide solution was added dropwise to the solution at a rate of 2 mL / min. Then, 7.5 mL of 0.12 M ascorbic acid solution was added dropwise to the solution at a rate of 0.4 mL / s. After stirring for 3 minutes, 7.5 mL of 0.12 M ascorbic acid solution was directly added and stirred at room temperature for 1 hour. The obtained nanoparticles were washed with ethanol and deionized water for three times, respectively, to finally obtain cuprous oxide (Cu2O) nanoparticles with a particle size of 140 nm; then 200 mg of cuprous oxide (Cu2O) nanoparticles and 1 mL of γ-aminopropyltriethoxysilane (APTES) were refluxed in 50 mL of dimethyl sulfoxide (DMSO) at 110°C, and the obtained Cu3O-NH2 nanoparticles were washed with ethanol and deionized water for three times, respectively;
[0050] (2) 200 mg of Cu3O-NH2 nanoparticles, 20 mg of polyvinyl amide (PEI) and 63 μL of acrylamide (AAM) obtained in step (1) were completely mixed and the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a yellow low-angle-dependent non-iridescent structural color film with a reflection wavelength of 569 nm. The reflection wavelength of the structural color film is similar to that of the photograph. Figure 5 As shown in Example 6.
[0051] Example 7
[0052] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.43 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally ferroferric oxide nanoparticles with a particle size of 142 nm were obtained. Then 200 m 1 g of ferrosoferric oxide nanoparticles were dispersed in 190 mL of acetonitrile (ACN) and ultrasonicated for 5 min. Then, 520 μL of ethyl acrylate (EA), 740 μL of hydroxyethyl methacrylate (HEMA), 300 mg of methylenebisacrylamide (MBA) and 30 mg of azobisisobutyronitrile (AIBN) were added and ultrasonicated for 10 min. Then, the dispersion was refluxed and precipitated at 110 °C for 2 h. The obtained Fe3O4@(PHEMA-co-PEA) nanoparticles were washed 3 times with ethanol and deionized water respectively.
[0053] (2) 200 mg of Fe3O4@(PHEMA-co-PEA) nanoparticles obtained in step (1) and 120 μL of hydroxyethyl methacrylate (HEMA) were thoroughly mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles was 70 wt % at this time, and the obtained mixed slurry was allowed to stand for 0, 0.5, 1, 2, 4, 7, 12, 24 and 30 hours, respectively. 20 mg of the slurry was taken in each time period and placed between two PET films, and then induced self-assembly under the shearing action of a double-roll mill to obtain a series of green low-angle-dependent non-iridescent structural color films, whose reflection wavelengths were 523, 535, 527, 519, 520, 525, 525, 526 and 521 nm, respectively. The reflection wavelengths and photos of the different structural color films are shown in Figure 2. Figure 6 shown.
[0054] Example 8
[0055] (1) 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O), 3.6 g of anhydrous sodium acetate (NaAc), 0.3 g of sodium citrate dihydrate (Na3Cit·2H2O), 0.41 g of sodium hydroxide and 35 mL of anhydrous ethylene glycol (EG) were mixed thoroughly and placed in a hydrothermal kettle. The mixture was kept at 190°C in a forced air oven for 8 hours. The obtained nanoparticles were washed three times with ethanol and deionized water respectively, and finally ferroferric oxide nanoparticles with a particle size of 170 nm were obtained. Then 200 m 1 g of ferrosoferric oxide nanoparticles were dispersed in 190 mL of acetonitrile (ACN) and ultrasonicated for 5 min. Then, 520 μL of ethyl acrylate (EA), 740 μL of hydroxyethyl methacrylate (HEMA), 300 mg of methylenebisacrylamide (MBA) and 30 mg of azobisisobutyronitrile (AIBN) were added and ultrasonicated for 10 min. Then, the dispersion was refluxed and precipitated at 110 °C for 2 h. The obtained Fe3O4@(PHEMA-co-PEA) nanoparticles were washed 3 times with ethanol and deionized water respectively.
[0056] (2) 200 mg of Fe3O4@(PHEMA-co-PEA) nanoparticles obtained in step (1) and 82 μL of hydroxyethyl methacrylate (HEMA) are thoroughly mixed, i.e., the mass fraction of Fe3O4@(PHEMA-co-PEA) nanoparticles is 70 wt % at this time. After the obtained mixed slurry is allowed to stand for 24 hours, 20 mg of the slurry is placed between two PET films, and then induced to self-assemble under the shearing action of a double-roll mill to obtain a red low-angle-dependent non-iridescent structural color film with a reflection wavelength of 687 nm. After the obtained structural color film is solidified, it is ground into powder, and then mixed with a transparent matrix such as PDMS to obtain a precursor, i.e., a non-iridescent structural color pigment. (Photos of the film coated on the substrate at different angles are shown in the figure below) Figure 7 shown).
[0057] Example 9
[0058] (1) 0.35 g of copper acetate monohydrate (Cu(AC)2·H2O), 0.63 g of sodium citrate dihydrate (Na3Cit·2H2O), and 1.5 g of polyvinylpyrrolidone (PVP) were dissolved in 100 mL of deionized water and 27 mL of ethylene glycol (EG). After stirring, 20 mL of 0.5 M sodium hydroxide solution was added dropwise to the solution at a rate of 2 mL / min. Then, 7.5 mL of 0.12 M ascorbic acid solution was added dropwise to the solution at a rate of 0.4 mL / s. After stirring for 3 minutes, 7.5 mL of 0.12 M ascorbic acid solution was directly added and stirred at room temperature for 1 hour. The obtained nanoparticles were washed with ethanol and deionized water for three times, respectively, to finally obtain cuprous oxide (Cu2O) nanoparticles with a particle size of 240 nm; then 200 mg of cuprous oxide (Cu2O) nanoparticles and 1 mL of γ-aminopropyltriethoxysilane (APTES) were refluxed in 50 mL of dimethyl sulfoxide (DMSO) at 110°C, and the obtained Cu3O-NH2 nanoparticles were washed with ethanol and deionized water for three times, respectively;
[0059] (2) 200 mg of Cu3O-NH2 nanoparticles, 20 mg of polyvinyl amide (PEI) and 63 μL of acrylamide (AAM) obtained in step (1) were thoroughly mixed and the obtained mixed slurry was allowed to stand for 24 hours. 20 mg of the slurry was placed between two PET films and then induced to self-assemble under the shearing action of a double-roll mill to obtain a red low-angle-dependent non-iridescent structural color film with a reflection wavelength of 720 nm. The obtained structural color film was solidified and then ground into powder to obtain a non-iridescent structural color pigment.
[0060] Example 10
[0061] (1) Dissolve 10g of polyvinyl pyrrolidone (PVP) in 150mL of deionized water. After the solution is completely dissolved, heat it to 80°C. Then add 200μL of nitric acid and 7.315g of thioacetamide (TAA) to the polymer solution and stir evenly for 10 minutes. Then, dissolve 2.97g of zinc nitrate hexahydrate in 50mL of deionized water, quickly pour it into a flask and stir vigorously at 80°C for 2 hours. The obtained nanoparticles are washed with ethanol and deionized water three times each, and finally zinc sulfide (ZnS) nanoparticles with a particle size of 120nm are obtained. Then, 200mg of zinc sulfide (ZnS) nanoparticles and 1mL of γ-aminopropyltriethoxysilane (APTES) are refluxed in 50mL of dimethyl sulfoxide (DMSO) at 110°C. The obtained ZnS-NH2 nanoparticles are washed with ethanol and deionized water three times each.
[0062] (2) 200 mg of ZnS-NH2 nanoparticles, 20 mg of polystyrene-maleic anhydride copolymer (PSSMA) and 63 μL of acrylamide (AAM) obtained in step (1) were thoroughly mixed. After the obtained mixed slurry was allowed to stand for 24 hours, 20 mg of the slurry was placed between two PET films. The mixture was then induced to self-assemble under the shearing action of a double-roll mill to obtain a blue non-iridescent structural color film having a reflection wavelength of 450 nm.
Claims
1. A method for preparing a non-iridescent structural color material with high saturation and high brightness, using inorganic nanoparticles with high refractive index as primitives, and small molecules mediated shear-induced self-assembly at room temperature to obtain a non-iridescent photonic crystal structural color film and pigment, the specific steps are: (1) Preparation of structural color paste The surface of inorganic nanoparticles with a high refractive index is modified, and then mixed evenly with a small molecule organic matrix to form a structural color paste with high viscoelasticity; (2) Preparation of non-iridescent structural color films and pigments The structural color slurry obtained in step (1) is allowed to stand to increase the interaction between the nanoparticles and the matrix, and then the slurry is sandwiched between two layers of PET, and a shear force is applied using a double-roll mill. After solidification, a non-iridescent structural color film is obtained, and the non-iridescent structural color pigment is obtained by grinding the film; The method for modifying the surface of the nanoparticles in step (1) is as follows: coating the nanoparticles with a polymer shell to form microspheres with a core-shell structure; the polymer is obtained by polymerization of hydroxyethyl methacrylate, acrylic acid, ethyl acrylate, methacrylic acid, butyl acrylate or isooctyl acrylate; The small molecule organic matrix in step (1) is selected from hydroxyethyl methacrylate, acrylic acid, ethyl acrylate, methacrylic acid, butyl acrylate, methyl methacrylate, methyl acrylate, and methylformamide.
2. The preparation method according to claim 1, characterized in that: The inorganic nanoparticles with a high refractive index in step (1) are selected from ferroferric oxide, cuprous oxide, zinc oxide, zinc sulfide, cadmium sulfide and titanium dioxide.
3. The preparation method according to claim 1, characterized in that: The particle size of the inorganic nanoparticles in step (1) is 100-300 nm.
4. The preparation method according to claim 1, characterized in that: The method for producing a highly viscoelastic structural color paste in step (1) is as follows: the modified inorganic nanoparticles and the organic matrix swell with each other or produce supramolecular effects; another component polymer that can increase the interaction between the nanoparticles and the matrix is added to the system, and the polymer is selected from polyethyleneimine and polystyrene-maleic anhydride copolymer.
5. The preparation method according to claim 1, characterized in that: The structural color slurry in step (2) is allowed to stand for 5 to 30 hours.
6. The preparation method according to claim 1, characterized in that: The distance between the two rolls of the double-roll mill in step (2) is 0.6-1 mm, so as to control the constant shear force.
7. The preparation method according to claim 1, characterized in that: The shear force applied in step (2) is 0.08-0.15 MPa.
8. A non-iridescent structural color material obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of structural color thin film
CN108855803A
Method for preparing low-angle-dependence structure developing film
CN110527124A